Pathological Mechanisms in Diabetes - Grau, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Diabetes is a worldwide public health problem that can be explained by the classic model of the determinants of health. Thus, success in preventing diabetes mellitus and its associated complications not only depends on the individual but also on social and community networks as well as general socioeconomic, cultural, and environmental conditions. For that reason, we need to create conditions that ensure good health and social care for an entire population through the development and implementation of preventive strategies, promotion of healthy lifestyles, protection from diseases, and the design of targeted screening strategies. This aligns with the United Nations Sustainable Development goal number 3, good health and well-being, which includes the achievement of universal health coverage and access to quality essential healthcare services. In addition, this also has a direct link to goal number 10, which focuses on reducing inequalities within and among countries. Pathological Mechanisms in Diabetes is a compilation of high-quality scientific evidence aimed at unraveling the molecular mechanisms involved in the association between diabetes and comorbidities and at describing their clinical and therapeutic implications. The variety of updated topics included from different approaches shows the need for more efficient preventive activities to reduce the incidence of this disease and its related complications.